Predictors of Atrial Fibrillation Recurrence after Catheter Ablation: Data from the German Ablation Registry. Issue 1 (December 2017) - Sultan, A.; Lüker, J.; Andresen, D.; Kuck, K.; Hoffmann, E.; Brachmann, J.; Hochadel, M.; Willems, S.; Eckardt, L.; Lewalter, T.; Senges, J.; Steven, D.
Abstract Catheter ablation (CA) for atrial fibrillation (AF) has emerged as a widespread first or second line treatment option. However, up to 45% of patients (pts) show recurrence of AF within 12 month after CA. We present prospective multicenter registry data comparing characteristics of pts with and without recurrence of AF within the first year after CA. This study comprises all pts with complete follow-up one year after CA (1-y-FU; n = 3679). During 1y-FU in 1687 (45.9%) pts recurrence of AF occurred. The multivariate analysis revealed female sex and AF type prior to the procedure as predictors for AF recurrence. Furthermore, comorbidities such as valvular heart disease and renal failure as well as an early AF relapse were also predictors of AF recurrence during 1-y-FU. However, despite an AF recurrence rate of 45.9%, the majority of these pts (72.4%) reported a significant alleviation of clinical symptoms. In conclusion in pts with initially successful CA for AF female sex, AF type, in-hospital AF relapse and comorbidities such as renal failure and valvular heart disease are independent predictors for AF recurrence during 1-y-FU. However, the majority of pts deemed their interventions as successful with significant reduction of symptoms irrespective of AF.